Comparative study of single dose preoperative antibiotics versus both preoperative and postoperative antibiotics in laparoscopic appendicectomy for nonperforated appendicitis - Bangaru, Himabindu; Gaiki, Varun V.; Reddy, M. V. Ranga (International Surgery Journal, 2017)
Background: Antibiotics are being administered both preoperatively and postoperatively even in uncomplicated nonperforated appendicitis. Studies regarding role of postoperative antibiotics in laparoscopic appendicectomy for nonperforated appendicitis are sparse. The aim of the study is therefore to study the efficacy of single dose preoperative antibiotics versus both preoperative and postoperative antibiotics in reducing surgical site infection in laparoscopic appendicectomy for uncomplicated nonperforated acute appendicitis. Methods: This is a prospective study done in general surgery department at Malla Reddy institute of medical sciences from September to April 2016.162 patients with nonperforated appendicitis were randomly allocated into two groups. 80 patients in Group A were given single dose of preoperative prophylactic antibiotics. No further antibiotics were given. 82 patients in Group B were given both preoperative and postoperative antibiotics. Postoperative surgical site infection and duration of postoperative hospital stay were compared between both groups. Statistical analysis was done using ANOVA, Fisher’s Exact test and Chi-square test wherever necessary. Results: There was no significant difference in the rate of surgical site infection in both groups. The mean duration of postoperative hospital stay was shorter in preoperative antibiotics only group (Group A). Age and gender had no significant association with surgical site infection. There was no deep incisional or organ space infection in this study. Conclusions: Single dose prophylactic antibiotics would be sufficient in cases of laparoscopic appendicectomy for simple uncomplicated nonperforated acute appendicitis. Postoperative antibiotic administration would not be necessary in these cases.